Optimism over despair on capitalism, empire and social change - Noam, Chomsky
This volume offers readers a concise and accessible introduction to the ideas of Noam Chomsky, described by the New York Times as ?arguably the most important intellectual alive.?
Formerly CIP.
Keywords: Chomsky, Noam -- Interviews